PARTISIPASI POLITIK PEMILIH PEMULA DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DI DESA SEKARAN KECAMATAN WONOSARI KABUPATEN KLATEN TAHUN 2024 - Astoko, Dudi Budi; Muslimin, Edy; Handayani, Triana Nur; Farhun, Awi (AL HAZIQ: Journal of Community Service, 2024)
First-time voters play a crucial role in the electoral process. This year, Indonesia conducted elections to choose members of the DPR, DPRD, President, Vice President, and DPD. In this election, particular attention is given to the participation of first-time voters, with an estimated 52% of young voters predicted to participate. However, the lack of awareness about democracy and low political education among first-time voters could potentially decrease voter turnout in the upcoming 2024 elections. Recognizing the importance of the participation of first-time voters, especially in the forthcoming elections, there is a need for community outreach and education on political participation, particularly targeting Sekaran Village in Wonosari Sub-District, Klaten Regency, which has a total of 64,760 registered voters. This community service initiative aims to enhance the awareness of first-time voters about the significance of political participation. The results of this initiative show an increase in awareness among young people, particularly first-time voters, as evidenced by their enthusiasm for fulfilling their electoral duties.